The NPC1L1 Polymorphism 1679CG Is Associated with Gallstone Disease in Chinese Patients - Wu, Jian; Cui, Wei; Cai, Qu; Fei, Jian; Zhang, Sheng-Dao; Han, Tian-Quan; Hu, Hai; Jiang, Zhao-Yan (PloS one, 2016)
Niemann Pick Type C1 Like 1 (NPC1L1) protein plays a key role in intestinal and hepatic cholesterol metabolism in humans. Genetic variation in NPC1L1 has been widely studied in recent years. We analyzed NPC1L1 single nucleotide polymorphisms in Chinese gallstone disease patients to investigate their association with gallstone disease. NPC1L1 mRNA expression was also measured in liver biopsies from patients with cholesterol gallstone disease and compared between genotypes. The G allele of the g1679C>G (rs2072183) polymorphism was significantly more prevalent in patients with gallstones compared with gallstone-free subjects. Moreover, patients carrying the G allele had lower hepatic NPC1L1 mRNA expression and higher biliary cholesterol (molar percentages) and cholesterol saturation index. Our study suggests that the G allele of the NPC1L1 polymorphism g1679C>G may be a positive marker of gallstone formation risk.